Elastic Rhythm in Signal-Synchronised Sequencing Objects for Pure Data - Kelly, Edward (Revista Vórtex, 2021)
This paper presents a family of objects for manipulating polyrhythmic sequences and isorhythmic relationships, in both the signal and event domains. These work together and are tightly synchronised to an audio phase signal, so that relative temporal relationships can be tempo-manipulated in a linear fashion. Many permutations of polyrhythmic sequences including incomplete tuplets, scrambled elements, interleaved tuplets and any complex franctional relation can be realised. Similarly, these many be driven with controllable isorhythmic generators derived from a single driver, so that sequences of different fractionally related lengths may be combined and synchronised. It is possible to use signals to drive audio playback that are directly generated, so that disparate sound files may be combined into sequences. A set of sequenced parameters are included to facilitate this process.